Evaluation of PACE4 isoforms as biomarkers in thyroid cancer - Laurent Fradet; Rabia Temmar; Frédéric Couture; Mathieu Belzile; Pierre-Hugues Fortier; Robert Day (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background To date, no single molecular marker has been demonstrated as clinically useful in differentiating malignant from benign thyroid nodules when a fine needle aspiration falls in the “unknown significance” categories of the Bethesda Classification. PACE4, a member of the proprotein convertase family of enzymes, has been shown to play a major role in the pathogenesis of prostate cancer, through the formation of an oncogenic isoform named PACE4-altCT. PACE4 isoforms have also been suggested to play a role in other cancers, including thyroid cancer, but have never been investigated in a detailed manner. Our objective is to compare the histochemical distribution of the two major PACE4 isoforms in benign and malignant thyroid nodules, in order to determine their potential usefulness as discriminatory biomarkers. Methods Thyroid tissues of patients who underwent thyroidectomy were classified according to final pathology. Corresponding tissue sections were immunostained, using two previously validated antibodies raised against the C-terminal end of the two PACE4 isoforms, namely the full-length PACE4 protein (PACE4-FL) and its alternative isoform (PACE4-altCT). Nodules were compared with adjacent normal parenchyma and immunostaining was rated as “low” or “high” by a head and neck pathologist. Results Non-lesional thyroid parenchyma did not express PACE4-FL (p = 0.002). As a group, malignant (n = 17) nodules expressed PACE4-FL significantly more than benign (n = 24) nodules (percentage of high immunostaining: 52.9% vs 4.2%; p = 0.001). Reciprocally, there was a statistically lower expression of PACE4-altCT in malignant nodules than in adjacent non-lesional parenchyma (p = 0.014). The specificity of a high PACE4-FL immunostaining in determining malignancy was 95.8% (95% CI, 78.9% to 99.9%). Conclusion This study supports the previously described relationship between PACE4-FL and PACE4-altCT through alternative splicing. It also suggests that PACE4-FL is a promising biomarker for thyroid malignancy. Its high specific expression for malignancy could make it an interesting “rule in” test for thyroid cancer. Further prospective, quantitative studies are currently being designed to address how measurements of PACE4 isoforms could be used in a clinical setting. Trial registration This study does not report the results of a health care intervention on human participants. It was nonetheless registered on ClinicalTrials.gov under reference number NCT03160482.